Design of an IoT-Based Automatic Weighing System for Catfish Farming to Support Smart Aquaculture - Jannah, Sutra Wardatul; Muhtadi, Ahmad; Ridwan, M. Deny; Kurlillah, Rizki (TIERS Information Technology Journal, 2024)
Enhancing the accuracy and efficiency of the catfish weighing process is essential for farmers to optimize distribution to retailers and wholesalers while improving productivity and operational performance. This study focuses on developing an IoT-based automatic weighing system to provide a real-time and automated solution to these challenges. The proposed system incorporates a load cell sensor for weight measurement, an ESP32 microcontroller with a WiFi module for seamless data transmission, and an intuitive web-based interface for monitoring and control. Powered by solar energy, the system emphasizes the integration of renewable energy in aquaculture. The research involves designing the system's mechanical, electrical, and software components to create a practical and accessible tool for farmers. Field trials on catfish farms assess the system’s performance in terms of accuracy and efficiency, comparing it to conventional manual weighing methods. This innovation aims to boost operational efficiency in aquaculture while contributing to the adoption of sustainable and intelligent farming technologies.